Edukasi Fisioterapi Stretching Pada Senam Prolanis Lansia di Puskesmas Sibela Kelurahan Mojosongo Surakarta - Refideso, Salim; Wahyuni; Charisa, Anis Dwi (Yayasan Sagita Akademia Maju, 2024)
Elderly people are individuals over 60 years old. The elderly is related to the aging process accompanied by physical, mental and social changes, which have an impact on health such as hypertension and diabetes mellitus. Stretching before exercise is to prevent injury, maintain the elasticity of muscles and tendons, thereby increasing the range of movement. Prolanis is a health service system and a proactive approach that is implemented in an integrated, involving manner. participants, health facilities and the Social Security Administering Agency (BPJS). The aim of this activity is to increase the effectiveness of prolanis exercise in the elderly and prevent injuries from occurring when carrying out prolanis exercise activities. The activity stages were given stretching education before starting prolanis exercises in the Sibela Community Health Center environment. The results obtained from prolanis exercise activities show that prolanis exercise is carried out 4 (four) times a month, education is given once in the second week to prolanis exercise participants through direct practical activities in the field before the exercise is carried out so that participants can understand the importance of stretching or stretching the muscles of the upper and lower limbs to prevent injury.